Life Sciences Genetic Engineering and Patent Rights. A Singapore Perspective - WEI, George S. S. (Institutional Knowledge at Singapore Management University, 2009)
Singapore has identified life science research as an important component of her economic and industrial growth strategy for her next phase of development. Not only is there strong Government support to encourage foreign biotechnology companies to locate in Singapore - there has also been on acute awareness of the need for discussion over regulation. The work of the Singapore Bioethics Advisory Committee in this area is particularly instructive and it can only be a question of time before the Singapore Patents System is asked to address issues on the interface between morality and patentability. This article surveys recent patent law developments in UK and Europe (and especially with reference to stem cells) and suggests that outside of the patent system, core regulation of the type of life science research to be permitted is best found outside of the patent system. Singapore is likely to adopt a light touch approach at least so far as patent law is concerned.